Character Internalization Based School Culture of Karangmloko 2 Elementary School - Husna Nashihin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Character education based school culture is very important to be developed at this time. Of the many schools that have implemented it, one of them is Karangmloko 2 Elementary School in Yogyakarta. This Field Research uses a Phenomenology approach which aims to describe the phenomenon of school culture as a basis for character education in Karangmloko 2. The results of this study indicate that character education based school culture of Karangmloko 2 done in three stages, namely; moral knowing, moral feeling, and moral action. The school culture of Karangmloko 2 is programmed (willed) consisting of 7 school cultures namely Lost and Found Box, Friday Action (AJUBER), Islamic Wall Magazine (MADIGAIS), My Dhuha Board, Honesty Cafeteria, Friday Gymnastics, and Friday Cleaning. The seven school cultures are capable to produce values of characters including Religion, Social Responsibility, Helping Each Other, Love Literacy, Learning Spirit, Discipline, Honesty, Responsibility, Caring for Health, Unity, and Caring for the Environment.تربية الشخصية القائمة على ثقافة المدرسة من المهم جدا أن يتم تطويرها في هذا الوقت. من بين العديد من المدارس التي نفذتها، واحدة منها هي مدرسة Karangmloko 2 الابتدائية في يوجياكرتا. يستخدم هذا البحث الميداني منهجًا لعلم الظواهر يهدف إلى وصف ظاهرة الثقافة المدرسية كأساس لتعليم الشخصية في Karangmloko 2. تشير نتائج هذه الدراسة إلى أن الثقافة المدرسية القائمة على تعليم الشخصية في Karangmloko 2 تتم على ثلاث مراحل، وهي: المعرفة الأخلاقية، والشعور الأخلاقي، والعمل الأخلاقي. تمت برمجة (إرادة) ثقافة مدرسة Karangmloko 2 وتتكون من 7 ثقافات مدرسية وهي: صندوق المفقودات والموجودات، جمعة الحركة (أجوبر)، مجلة الجدار الإسلامي (MADIGAIS)، بلدي مجلس الضحى، كافتيريا الصدق، جمباز الجمعة، و تنظيف الجمعة. إن الثقافات المدرسية السبعة قادرة على إنتاج قيم من الشخصيات ، بما في ذلك الدين والمسؤولية الاجتماعية ومساعدة بعضنا البعض ومحو الأمية وروح التعلم والانضباط والصدق والمسؤولية ورعاية الصحة والوحدة ورعاية البيئة.